PROBLEMS OF INFORMATION-PSYCHOLOGICAL SECURITY OF SOCIETY IN THE CONTEXT OF ENSURING NATIONAL INTERESTS OF RUSSIA IN THE INFORMATION SPHERE - Dmitry V Yurkov (RUDN Journal of Public Administration, 2016)
At the present stage of the development of social relations the information acquires the value of the most important resource in global policy and world economy. At this conjuncture the global information sphere becomes an arena of inter-state confrontation using the methods of information-psychological war. The scientific attitudes to the definition of the term “information-psychological war” are considered in the article on the base of Russian and foreign materials. The course of and interim results of the informational opposition between Russia and the block of the Western states is analyzed in relation to the political crisis in Syria and Ukraine. According to the author, the transition to “positional information war” based on using “the image of the enemy” is dangerous because of the rise of chauvinistic moods and serious deterioration of international relations. The author considers that the realization of the state information policy must be based on the long-term national interests.